Evaluation of different strains of Spirulina on selected culture media as potential feed supplement for broiler - Abdul Ghofar, Hasfar Syafiqah (2019)
Poultry is one of the important livestock industries and has become the staple meat in Malaysia. Due to high demand, the production for the broiler had increased and has met the level of self-sufficiency with the aid in technological progress in animal husbandry, particularly nutritional aspect. A variety of synthetic feed additives has been used to maximize the production. However, due to public concern on the antibiotic residues in the meat, the feed business tends to use natural ingredients as supplement. Spirulina (Athrospira sp.) is a planktonic photosynthesis filamentous cyanobacterium consists of highly nutritious, a potential feed resource for many agriculturally important animal species. In this work, five difference strains of Spirulina sp.; Spirulina platensis TBSH1- 5, Spirulina platensis TBSHX-1, Spirulina platensis M1, Spirulina maxima, Spirulina platensis were grown on three different culture media, namely; Zarrouk media, OFERR media and Revised media (6). The growth rate and dry weight after 30 days of cultivation was determined. No significant difference was shown to be affected by the either strains nor medias on the growth and dry weight but with more outstanding results in the OFERR media and Revised medium (6). Large scale cost production of Spirulina is expensive; thus, it is more cost effective to use a cheaper medium. Animal wastewater has demonstrated to be one of the best nitrogen sources to produce a low-cost medium. Therefore, Spirulina was cultivated in four different sources of wastewater, namely; goat, poultry, seawater and tap water at dilution of 25%, 50%, 75% and 100% for 30 days. Cultivation of Spirulina sp. in difference wastewater was found to significantly (P<0.05) affected by different type of wastewater with more growth of Spirulina was notified in goat wastewater and tap water at 25% dilution. The similar result was also observed on dry weight, where seawater was found to be significantly higher compared to another wastewaters, 0.27 g (25%), 0.29 g (50%), 0.18 g (75%) and 0.08 g (100%) respectively, followed by tap water and goat wastewater medium. The in-vitro fermentation analysis was carried out by incubating the commercial diet supplemented with Spirulina platensis and Spirulina platensis TBSH-5 with cecal digesta of broiler for 72 hours at 39±5 ⁰C. The gas production and end products of the fermentation were examined. Commercial starter and finisher diet supplemented with or without Spirulina platensis TBSH1-5 and Spirulina platensis has demonstrated that interaction between treatment and Spirulina strains has no significant. While, the in-vitro dry matter degradability of both starter and finisher diet were improved (P<0.05), with more outstanding results observed in the Spirulina sp. supplementation at 0.25 g and 0.75 g. Thus, it is suggested that Spirulina has a potential to be used as a supplement for poultry when it is cultivated in dilution of media with tap water and a better digestibility when supplemented at 0.75 g (starter) and 0.25 g (finisher).